The epidemiology of asthma in Mainland China: a systematic review and meta-analysis - Jiarui Yu; Liang Xu; Azhu Han; Maomao Xie (BMC, 2024)
Abstract Background Reliable estimates of asthma prevalence are essential for developing effective public health policies. However, discrepancies in published results have posed challenges for public health planning in China. To address this issue, we conducted this study to provide a comprehensive assessment of the epidemiology of asthma prevalence in China. Methods We conducted a thorough systematic review across multiple databases including PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Data, and Weipu database. The search was limited to studies published in either Chinese or English up to August 31, 2023, that reported on asthma prevalence in China. We extracted relevant study characteristics and performed meta-analyses. The study protocol was registered with PROSPERO (CRD42023397949). Results A literature search yielded 192 studies that met the inclusion criteria out of 17,152 articles. The overall prevalence of asthma in Mainland China was found to be 2.20% (95% confidence interval, CI: 1.96-2.47%; I 2 = 99.8%), with the prevalence of ever asthma at 2.21%, current asthma at 2.16%, ever asthma-like symptoms at 14.36%, and current asthma-like symptoms at 3.01%. Using a random-effects model, the prediction interval ranged from 0.44 to 10.27%. Meta-analysis subgroups indicated that men or children and the elderly generally have a higher prevalence of asthma. In addition, the prevalence of asthma is higher in urban areas and in the East China. The prevalence of asthma has been on the rise over the past three decades, from 0.69% in 1984 to 5.30% in 2021. Projections suggest that the prevalence could reach 9.76% by 2050 for the Chinese population. Conclusions Asthma remains less prevalent in China than in western countries, however its prevalence has been gradually increasing over the past thirty years. The disease burden shows notable variations based on sex, age, and geographic regions, indicating significant demographic and regional disparities. To guide decision-making priorities and direct future research, conducting high-quality epidemiological studies on asthma is crucial.